АДМІНІСТРАТИВНО-ПРАВОВІ МЕТОДИ ЗАПОБІГАННЯ ТА ПРОТИДІЇ ЗЛОЧИННОСТІ ОРГАНАМИ ДЕРЖАВНОЇ МИТНОЇ СЛУЖБИ УКРАЇНИ - ЧЕРКАССЬКИЙ, Руслан Анатолійович (SUPREMANCE OF LAW, 2016)
The article, based on the analysis of scientific views of scientists and current legislation of Ukraine, identifies the following administrative and legal methods of combating and preventing crime by the State Customs Service: a) methods used in terms of planning the work of the State Customs Service of Ukraine; b) methods of prevention and cessation of customs offenses; c) measures to combat smuggling. It is emphasized that the administrative and legal methods of counteraction and prevention ofcrime outlined by the State Customs Service outlined in the presented scientific article most characterize in detail and meaningfully what tools the researched department uses in the process of its activities in relevant areas. It is emphasized that the list of methods outlined in the paper is not exhaustive, and therefore, the legislator and scientists should work to expand their list and content.
Keywords: administrative and legal methods; counteraction and prevention ofcrime; State Customs Service